El proceso analítico, considerando lo aritmomórfico, la aducción y la complejidad. La importancia de la investigación teórica en la ciencia económica: Reflexiones sobre la contribución de Georgescu-Roegen - Cisneros García, Juan Manuel Eliud (2015)
The notion of analytical process is essential to understand the task of theoretical research in Economic Science, because it is explicable only those items that can be expressed as a process. The explanation for a set of social facts related to any economic activity only can be performed with a theory, which arises considering an analytical process. The complexity of social reality must be simplified by abstraction, this requires to recognize two fundamental notions: the aritmomorphic and the adduction. The issues raised in this paper are based on the epistemological proposal developed by Georgescu-Roegen.